Practical guide to moderate sedation/analgesia. - Odom-Forren, Jan.; Watson, Donna; Watson, Donna (St. Louis, Mo. : Elsevier Mosby, 2005)
"This easy-to-follow book is your complete clinical guide to caring for patients receiving conscious sedation/analgesia during a short-term therapeutic, diagnostic, or surgical procedure. It covers everything you need to know - from practice guidelines for administering sedation, to pre-sedation requirements, intra-procedure monitoring and documentation, and discharge criteria."--BOOK JACKET.
Rev. ed. of: Conscious sedation/analgesia / Donna S. Watson. c1998.
Keywords: Analgesia; Conscious sedation; Intravenous anesthesia; Nurses; Conscious Sedation; Analgesia